Exploring the Connections: Autophagy, Gut Microbiota, and Inflammatory Bowel Disease Pathogenesis - Subramanian A; J A; T T; Kumarasamy V; Begum MY; Sekar M; Subramaniyan V; Wong LS; Al Fatease A (Journal of Inflammation Research)
Arunkumar Subramanian,1 Afrarahamed J,1 Tamilanban T,1,2 Vinoth Kumarasamy,3 M Yasmin Begum,4 Mahendran Sekar,5 Vetriselvan Subramaniyan,6 Ling Shing Wong,7 Adel Al Fatease4 1Department of Pharmacology, SRM College of Pharmacy, SRM Institute of Science and Technology, Kattankulathur, Tamilnadu, India; 2Faculty of Medicine, Bioscience and Nursing, MAHSA University, Selangor, Malaysia; 3Department of Parasitology & Medical Entomology, Faculty of Medicine, Universiti Kebangsaan Malaysia, Jalan Yaacob Latif, Cheras, Kuala Lumpur, Malaysia; 4Department of Pharmaceutics, College of Pharmacy, King Khalid University, Abha, Saudi Arabia; 5School of Pharmacy, Monash University Malaysia, Bandar Sunway, Subang Jaya, Selangor, Malaysia; 6Department of Medical Sciences, School of Medical and Life Sciences, Sunway University, Bandar Sunway, Selangor, Malaysia; 7Faculty of Health and Life Sciences, INTI International University, Nilai, MalaysiaCorrespondence: Tamilanban T; Vinoth Kumarasamy, Email tamilant@srmist.edu.in; vinoth@ukm.edu.myAbstract: Inflammatory Bowel Disease (IBD), which includes Crohn’s disease and ulcerative colitis, represents a complex and growing global health issue with a multifaceted origin. This review delves into the intricate relationship between gut microbiota, autophagy, and the development of IBD. The gut microbiota, a diverse community of microorganisms, plays a vital role in maintaining gut health, while imbalances in this microbial community, known as dysbiosis, are linked to IBD. Autophagy, a process by which cells recycle their components, is essential for gut homeostasis and the regulation of immune responses. When autophagy is impaired and dysbiosis occurs, they individually contribute to IBD, with their combined impact intensifying inflammation. The interconnectedness of gut microbiota, autophagy, and the host’s immune system is central to the onset of IBD. The review also examines how diet influences gut microbiota and its subsequent effects on IBD. It highlights the therapeutic potential of targeting the microbiota and modulating autophagic pathways as treatment strategies for IBD. Understanding these interactions could lead to personalized therapies within the rapidly advancing fields of microbiome research and immunology. Keywords: inflammatory bowel disease, gut microbiota, autophagy, Crohn’s disease, ulcerative colitis